2022
DOI: 10.2147/jir.s347231
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyunsaturated Fatty Acids and Their Metabolites Regulate Inflammation in Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a blinding eye disease, whose incidence strongly increases with ages. The etiology of AMD is complex, including aging, abnormal lipid metabolism, chronic inflammation and oxidative stress. Long-chain polyunsaturated fatty acids (LCPUFA) are essential for ocular structures and functions. This review summarizes the regulatory effects of LCPUFA on inflammation in AMD. LCPUFA are related to aging, autophagy and chronic inflammation. They are metabolized to pro-and anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 221 publications
(234 reference statements)
1
18
0
Order By: Relevance
“…Consistent with previous studies, which showed an antiinflammatory diet alleviated retinopathy in aged or diabetic participants, we found a diet with anti-inflammatory potential was associated with a decreased prevalence of retinopathy in DM or aged participants. Adherence to a Mediterranean diet or antioxidant supplement with Omega-3 unsaturated fatty acids and vitamins could improve age-related macular degeneration and DR (12)(13)(14)(15)(16)(17). DII is an integrated index to evaluate dietary inflammatory potential, which might synthetically reflect consumption lifestyle and give instructions to patients at high risk of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, which showed an antiinflammatory diet alleviated retinopathy in aged or diabetic participants, we found a diet with anti-inflammatory potential was associated with a decreased prevalence of retinopathy in DM or aged participants. Adherence to a Mediterranean diet or antioxidant supplement with Omega-3 unsaturated fatty acids and vitamins could improve age-related macular degeneration and DR (12)(13)(14)(15)(16)(17). DII is an integrated index to evaluate dietary inflammatory potential, which might synthetically reflect consumption lifestyle and give instructions to patients at high risk of retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between omega-3 and omega-6 LCPUFs seems to be of importance in preventing chronic low-grade inflammation. However, whether dietary supplementation with omega-3 LCPUFAs is protective for AMD is still under investigation D.C. Zysset-Burri et al (Jiang et al, 2021;Ren et al, 2022;Roh et al, 2020). Similar to carotenoids, humans obtain omega 3 and omega 6-LCPUFA only through diet, such as certain fatty fish, flax seeds and algae (Harauma et al, 2017).…”
Section: The Influence Of Diet On Age-related Macular Degenerationmentioning
confidence: 99%
“…Increased oxidative stress generated by oxidation of lipids also plays a role in the occurrence of AMD [ 87 , 88 ]. Carnitine is a dipeptide facilitating the transport of fatty acids into the mitochondria to oxidate.…”
Section: Application Of Metabolomics In Ocular Diseasesmentioning
confidence: 99%